Pola Penggunaan Omeprazole pada Pasien HIV & AIDS di UPIPI RSUD DR. Soetomo Surabaya - Ariana, Dona; Trijono, Erwin Astha; Surdijati, Sri; Nathalia, Aditya (Faculty of Pharmacy, Widya Mandala Surabaya Catholic University, Indonesia, 2018)
Human Immunodeficiency Virus (HIV) is a virus that spreads through body fluids and attacks the immune system, especially CD4 + lymphocyte-T cells (CD4). AIDS is a retroviral disease characterized by severe immune suppression that causes opportunistic diseases, secondary neoplasms, and neurological disorders. Patients suffering from chronic diseases, such as HIV & AIDS patients may experience severe shocks or trauma. This condition can trigger the release of excessive stomach acid to experience erosion or acute gastric ulcers with bleeding. This injury is classified as a gastric ulcer. Treatment of ulcers is needed, because a continuous ulcer can cause bleeding. Gastrointestinal bleeding can manifest in the direction of melena and hematemesis. The therapy that can be used is omeprazole which is a class of proton pump inhibitors. Omeprazole can prevent mucosal damage from gastric acid and can inhibit excess acid production from gastric parietal cells. This study aims to present omeprazole therapy data which includes dosage, route of drug administration, duration of use and qualitative analysis of interactions related to medical record data at UPIPI Hospital Dr. Soetomo Surabaya. The research method used was observational retrospective on the medical record of patients with HIV & AIDS. Sampling was carried out from January 1 to December 31, 2015. The results showed that omeprazole was the most widely used gastric ulcer drug in HIV & AIDS patients, as many as 56 patients (91.80%). The most frequent doses, frequencies, and routes were omeprazole 40 mg 2x1 IV in 55 patients (90.16%). Omeprazole therapy was given to patients with HIV & AIDS at UPIPI Hospital Dr. Surabaya Soetomo, regarding the dosage, frequency, route, and duration of administration are in accordance with existing guidelines.